A 5-year review of stillbirths and maternal Obesity in Hospital Sultanah Bahiyah Alor Setar Kedah (retrospective study 2011-2015) - Ahmad, Siti Sarah (2018)
Obstetric and Gynaecology Department Hospital Sultanah Bahiyah Alor Setar, Department of Obstetric and Gynaecology, School of Medical Sciences, University Sains Malaysia. Stillbirth account for a large part of all perinatal death. It has various definition across the country and region. The WHO defines stillbirth as the birth of baby at or after 28 weeks who died before or during labour and birth. The prevalence of obesity is increasing worldwide and had many implications on pregnancy and perinatal outcome.WHO uses body mass index (BMI) (weight(kg)/height(m)2) to define overweight and obesity. Overweight is defined as a BMI of 25 or more. Obesity can be divided into 3 category; BMI of 30.0-34.9 class 1 obesity, BMI 35.0-39.9 class 2 obesity, BMI 40.0 and over class 3 or morbid obesity. To determine the proportion of stillbirth among obesity mothers, to establish and look for the incidence of obesity among mother who experience stillbirth in Hospital Sultanah Bahiyah Alor Setar and to determine the risk and association of stillbirth among obese mother. A retrospective study was conducted in the Obstetrics and Gynaecology Unit, Hospital Sultanah Bahiyah Alor Setar for a period of 5 years (January 2011- December 2015) involving 350 pregnant women who delivered singleton pregnancy ( stillbirth) at 22 weeks of gestation or more with birth weight more than 500gm and fulfilled the inclusion and exclusion criteria. The overall mean fetal weight during delivery is 1630.00gm with median interquartile range (IQR is 1605.00). The mean age of mother during booking is 30 years old (SD: 6.12). They were at the age group of 20-30 years old (51.2%), followed by 31-40 years old (39.4%). 331 patient out of 350 (94.6%) is Malay, then 4.0% is chinese, and 1.4% is Indian. Majority of them 65.4% is multipara and 34.6% is primipara. 42 out of 350 patient (12%) who experience stillbirth is having BMI > 30mg/ m2 during booking which further divided to obesity class 1,22 patients (6.3%) , obesity class 2 , 14 patients (4.0%) and obesity class 3, 6 patient (1.7%) respectively. Only 5 patients (1.4%) is underweight while 16% of them is overweight (BMI >25mg/m2). Among obese women 6.6% of them in the age group of 31-40 years old , followed by 3.1% from age group of 21-30 years old and 2% of them is more than 41 years old. We can conclude that the prevalence of obesity is increase according to the age of patient . The occurrence of obesity is higher among multipara (9.1%) if compared to primipara (2.9%). 327 out of 350 patients (93.4%) didn’t have hypertension prior or during pregnancy. 4.6% (16) have gestational hypertension, while 1.4% (5) who have pre existing hypertension. 18 patient (6.0%) of them having gestational diabetes mellitus and 5 (1.4%) of patient is known to have diabetes mellitus prior to pregnancy.The incidence of essential hypertension in obese group was 0.6% and 0.9% is among non obese patient. While 3.7% of non obese patient suffered from gestational hypertension. Only 0.9% of obese patients were affected. The incidence of gestational diabetes mellitus among obese is 0.6% and 5.4% of non obese patient. Risk factors that associated with stillbirth among obese mother is related to maternal age. Based on maternal age, mother with 1-year increase in age will have 13% higher odds of having stillbirth (95% CI 1.07, 1.19, p<0.001) when adjusted for auto-immune disease. Those patient who pre pregnancy is having auto-immune disease will have 17% higher odds of having stillbirth (95% CI 2.89, 10.03, p=0.002) when adjusted for patients’ age. Maternal obesity is associated with increased risks of both maternal and neonatal complications, thus early recognition and prompt management is essential in order to improve maternal and neonatal outcome.